The Relationship Of Husband's Support And The Role Of Health Worker On Interest In Choosing Iud Contraception In The Mopah Baru Health Center Area - Yuslina Simangunsong; Candra Wahyuni; Reni Yuli Astutik; Erma Retnaningtyas (Journal of Health Science Community, 2024)
In Indonesia, many women experience difficulty in choosing the type of contraception. Factors that influence a mother in choosing an intrauterine contraceptive device (IUD) are family support, especially her husband, and the role of health workers especially midwives. This study aims to determine the relationship between husband's support and the role of health workers on interest in choosing IUD contraception in the Mopah Baru Community Health Center area. This research uses a research design Analytical Observational. With technique accidental sampling A sample of 42 respondents was obtained. Statistical tests are used Chi-Square to find out the relationship between the two variables. Data analysis found that there was a relationship between husband's support and interest in choosing IUD contraception, namely p value = 0.023 < 0.05, and there was no relationship between the role of health workers and interest in choosing IUD contraception, namely p value = 0.167 > 0.05. The need for husband's support for wives in choosing IUD contraception emotional, instrumental, appraisal, and informational support.